Liver abscess: study of etiological factors and different treatment modalities and their clinical implications - Khosla, Abhishek; Ali, Iqbal; Shetty, Varun (International Surgery Journal, 2019)
Background: Hepatic abscess (HA) can be defined as an encapsulated collection of suppurative material within the liver parenchyma, which may be infected by bacterial, fungal, and/or parasitic micro-organisms. The development of new radiologic techniques, the improvement in microbiologic identification, and the advancement of drainage techniques, as well as improved supportive care, have reduced mortality to 5-30%. The study is undertaken to study the etiology and the impact of the modern methods of treatment on the morbidity and mortality on the different types of liver abscess.. Methods: This study was a Prospective Study conducted from July 2016 to September 2018. Participation in the study was purely voluntary. Results: Majority of the patients (29%) were in the age group of 31-40 years with a male preponderance (91%). Diabetes mellitus was a common comorbidity in study subjects. Alcohol consumption was found as a significant risk factor in the development of liver abscess. Sixty eight (68%) patients underwent percutaneous needle aspiration and 27 (27%) patients were managed conservatively. Five (5%) patients required surgical intervention. Four (4%) patients died while 97 (97%) patients survived; 3 (3%) patients had undergone surgery while 1 (1%) patient was percutaneously drained. Conclusions: The most common age group affected by liver abscess was third and fifth decade of life . Males are more commonly affected than females. In case of larger (>5 cm) or 150 ml, Ultrasound guided percutaneous pigtail catheter drainage is a superior therapeutic approach than percutaneous needle aspiration. Surgical intervention is reserved for unresponsive cases.